Combination Olaparib and Temozolomide for the Treatment of Glioma: A Retrospective Case Series. (25th October 2022) - Schaff, Lauren R.; Kushnirsky, Marina; Lin, Andrew L.; Nandakumar, Subhiksha; Grommes, Christian; Miller, Alexandra Michelle; Gavrilovic, Igor T.; Nolan, Craig; Pentsova, Elena; Mellinghoff, Ingo K.; Kaley, Thomas J.
Abstract : Background and Objectives: To report the tolerability and efficacy of olaparib with temozolomide (TMZ) for glioma. Methods: Single-center retrospective series of patients with glioma treated with olaparib/TMZ from September 2018 to December 2021. Results: Twenty patients (median age: 42 years, median Karnofsky Performance Status: 90) received olaparib/TMZ for diagnoses of IDH -mutant oligodendroglioma (n = 5), IDH- mutant astrocytoma grade 2–3 (n = 4), IDH -mutant astrocytoma grade 4 (n = 7), or IDH- wildtype glioma (n = 4). One patient was treated upfront and 19 at recurrence (median = 3). Olaparib 150 mg was administered 3 times/week concurrent with TMZ 50–75 mg/m 2 daily. Fatigue, gastrointestinal symptoms, and hematologic toxicity were common. Six of 20 patients required dose reduction (n = 4) or discontinuation (n = 2) due to toxicity. Radiographic response was evaluable in 16 and observed (complete + partial) in 4/8 with IDH -mutant grade 2–3 glioma. No responses were seen in patients with grade 4 IDH -mutant astrocytomas (0/5) or IDH -wildtype gliomas (0/3). Progression-free survival was 7.8, 1.3, and 2.0 months, respectively. Discussion: Olaparib/TMZ resulted in objective radiographic response in 50% of evaluable patients with recurrent IDH -mutant grade 2–3 gliomas with encouraging progression-free survival and manageable toxicity. This supports a prospective trial of olaparib/TMZ for this population. Classification of Evidence: This case series provides Class IV evidence that treatment with olaparib/TMZ may result in radiographic response in patients with glioma.